Use f(x) = 2x − 3 and g(x) = 6 − x2 to evaluate the expression. (a) f(g(−

Algebra
Tutor: None Selected Time limit: 1 Day

Use 
f(x) = 2x − 3
 and 
g(x) = 6 − x2
 to evaluate the expression.
(a)   
f(g(−1))
 
 

(b)   
g(f(−1))
 

Jun 30th, 2015

Hi !

f(x) = 2x - 3

g(x) = 6 - x^2

(a) 

f(g(x)) = 2(6 - x^2) - 3

f(g(-1)) = 2(6 - (-1)^2) - 3

            = 2(6 - 1) - 3

            = 2(5) - 3

            = 10 - 3

           = 7

(b)

g(f(x)) = 6 - (2x - 3)^2

g(f(-1)) = 6 - (2(-1) - 3)^2

            = 6 - (- 2 - 3)^2

            = 6 - (- 5)^2

            = 6 - 25

            = - 19

Hope you get it. Thanks :)
Jun 30th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Jun 30th, 2015
...
Jun 30th, 2015
Mar 24th, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer